2020
DOI: 10.1177/2165079919897693
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Presence of Post-Traumatic Stress and Turnover Intention Among Nurses Post–Middle East Respiratory Syndrome Outbreak: The Importance of Supervisor Support

Abstract: Background: South Korea faced the Middle East Respiratory Syndrome (MERS) outbreak for the first time in 2015, which resulted in 186 infected patients and 39 deaths. This study investigated the level of posttraumatic stress disorder (PTSD) and turnover intention, the relationship between PTSD and turnover intention, and the buffering effect of supervisor support among nurses post-MERS outbreak. Methods: In total, 300 nurses from three of 15 isolation hospitals in South Korea were invited to participate. We col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
168
4
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(185 citation statements)
references
References 28 publications
9
168
4
4
Order By: Relevance
“…Furthermore, we found that hospital teams can impact HWs’ wellbeing, both positively and negatively. During the MERS pandemic, increased comradery among colleagues [ 34 , 40 ] and supervisor support [ 34 , 41 ] were also found to improve HW morale and resiliency. Providing resources that foster team bonding and assist with conflict resolution are important to improve HWs’ experiences during the COVID-19 pandemic and future outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that hospital teams can impact HWs’ wellbeing, both positively and negatively. During the MERS pandemic, increased comradery among colleagues [ 34 , 40 ] and supervisor support [ 34 , 41 ] were also found to improve HW morale and resiliency. Providing resources that foster team bonding and assist with conflict resolution are important to improve HWs’ experiences during the COVID-19 pandemic and future outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was also seen following MERS, with one study in South Korea demonstrating 57% of nurses suffered PTSD. 62 Overall, while being a HCW confers some psychologically protective elements, the evidence suggests being a HCW leads to worse outcomes. 59 NICE recommends assessment for all who have sustained trauma, using active monitoring to follow-up with subthreshold symptoms and offer cognitive behavioural therapy, cognitive processing therapy or eye movement desensitisation and reprocessing in those who are symptomatic in the postacute and intermediate phases.…”
Section: Psychological Sequelae and Rehabilitation Recommendationsmentioning
confidence: 99%
“…For GAD-7 the scores were classified as; normal (0-4), mild (5-7), moderate (8)(9)(10)(11)(12)(13)(14) and severe (15)(16)(17)(18)(19)(20)(21). For the PHQ-9 scores; normal (0-4), mild (5-9), moderate (10)(11)(12)(13)(14) and moderately severe (15)(16)(17)(18)(19) and severe (20)(21)(22)(23)(24)(25)(26)(27). These cut-offs have been well established in the literature [36][37][38].…”
Section: Outcomes and Covariatesmentioning
confidence: 99%